Rare-earth elements modelling of the Langkawi granites - Wan Fuad Wan Hassan,; Azman A. Ghani ,; Syafrina Ismail , (Universiti Kebangsaan Malaysia, 2001)
Based on the REE patterns the Langkawi granites can be divided into two groups i.e. the Gunung Raya-Dayang Bunting granite and Kuah-Pulau Tuba granite. The Gunung Raya-Dayang Bunting granite has weak negative Eu anomalies whereas the Kuah-Pulau Tuba granite has moderately strong negative Eu anomalies. Rb/Sr ratios also show similar differences with Rb/Sr ratios in Kuah-Pulau Tuba granites being much higher than those of the Gunung Raya-Dayang Bunting granite. Examination of the REE patterns shows that they have the usual 'bird-wing' shape with weak to moderately strong negative Eu anomalies. This pattern is similar to the West coast S-type granites and is different from the I-type granites of the East coast. A possible source material for the Langkawi granite is the Cambrian sediments of the Machinchang Formation. Modelling of the REE pattern has been carried out in two stages namely batch melting and fractional crystallisation. Results show that the Gunung Raya-Dayang Bunting magma requires a slightly higher degree of partial melting fraction (0.15-0.25%) compared to the Kuah-Pulau Tuba magma (0.25-0.3%). On the other hand the Gunung Raya/Dayang Bunting magma has undergone a higher degree of fractionation (16%) compared to the Kuah-Pulau Tuba magma (9%).